Progress and Prospects of Interleukin-22 in the Treatment of Non-alcoholic Fatty Liver Disease - Pan, Yuhao; Yu, Zebo (Journal of Contemporary Medical Practice, 2025)
Non-alcoholic fatty liver disease (NAFLD), also known as metabolism-associated fatty liver disease (MAFLD), has turned into the most prevalent chronic liver disease all over the world, with a complex pathogenesis and a lack of specific therapeutic agents. Interleukin-22 (IL-22), as a cytokine, plays a crucial role in liver physiology and pathology. The aim of this paper is to review the prospects and outlook of interleukin-22 (IL - 22) in the treatment of NAFLD, introduce the biological functions of IL - 22, discuss its mechanism of action in NAFLD, including its regulatory effects on liver inflammation, liver fibrosis, and lipid metabolism, etc., and analyse the current research advances on the treatment of NAFLD based on IL - 22, the challenges it faces, and the possible directions for future development.